Factors of Social and Psychological Adaptation to Studying Process at Higher Education Institutions in Students with Limited Health Opportunities - Huliaieva, Olena; Myloslavska, Olena; Bohdanovskyi, Serhii (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2023)
The article presents the results of a study devoted to the description of the socio-psychological characteristics of students with disabilities, which influence the success of adaptation to learning in higher education institutions, and also establishes the factor structure of socio-psychological adaptation to learning of students in this category. Two groups of subjects were compared: adapted and less adapted students. As a result of the study, it was found that adapted students with disabilities are characterized by developed social and communicative competencies, orientation towards professional growth and a career in the future against the backdrop of a significant decrease in intellectual and cognitive skills motives expressed in the desire for knowledge and mastery of a profession. Factor structure of socio-psychological adaptation of adapted students with disabilities represents an adequately developed personal-communicative potential, assimilative adaptation to the student group with the goal of overcoming existential needs and a specific manifestation of activity aimed at supporting self-conceptual integrity.